2015
DOI: 10.4081/mrm.2015.295
|View full text |Cite
|
Sign up to set email alerts
|

Beirut Air Pollution and Health Effects - BAPHE study protocol and objectives

Abstract: Background: Recent studies investigating the health effects of air pollution have proven an existing impact aroundand below international air quality guidelines and standards. These studies were based on accessible data from official registers managed by public authorities. The protocol followed in BAPHE project is described; its benefits and disadvantages are presented and discussed in this paper. Methods: Based on the review of several international studies we developed a custom made approach in BAPHE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that annual ambient average levels of particulate (PM 2.5 , PM 10 ) and NO 2 exceeded the air quality guidelines of the World Health Organization (WHO) (30.3 vs 10 μg m −3 , 51.3 vs 20 μg m −3 , and 53 vs 40 μg m −3 , respectively). 12,13 Also, vehicular traffic accounts for 27.1% of the total carbon dioxide (CO 2 ) emissions-which is 1.4 times higher than the world average of the total energy consumed by the road sector. 1 Air pollution in Lebanon is an environmental burden and a major source of concern to public health.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that annual ambient average levels of particulate (PM 2.5 , PM 10 ) and NO 2 exceeded the air quality guidelines of the World Health Organization (WHO) (30.3 vs 10 μg m −3 , 51.3 vs 20 μg m −3 , and 53 vs 40 μg m −3 , respectively). 12,13 Also, vehicular traffic accounts for 27.1% of the total carbon dioxide (CO 2 ) emissions-which is 1.4 times higher than the world average of the total energy consumed by the road sector. 1 Air pollution in Lebanon is an environmental burden and a major source of concern to public health.…”
Section: Introductionmentioning
confidence: 99%
“…The city of Beirut was chosen because of the availability of air pollution data. 36 The selected hospitals were chosen due to their proximity to pollutant measuring stations, the presence of an ED and their reception of large volumes of patients. The data sample was selected from a larger database collected for the Beirut Air Pollution and Health Effects (BAPHE) study performed by Nakhlé et al 36…”
Section: Sample Selectionmentioning
confidence: 99%
“…The data collection process is described in detail by Nakhlé et al in another study. 36 The data was collected using Microsoft Excel, inspected by the principal investigator, and validated by two senior physicians/epidemiologists.…”
Section: Data Collectionmentioning
confidence: 99%
“…A convenience sample of 3 hospitals with emergency departments located in densely populated areas in the city of Beirut was chosen. The city of Beirut was chosen because of the availability of air pollutant level monitoring performed in previous research studies [26]. The selected hospitals, Hotel Dieu de France (HDF), Saint Georges University Medical Center (SGHUMC) and Makassed Hospital, were chosen based on their location close to where pollutant monitoring was performed, the presence of an ED and their reception of large volumes of patients.…”
Section: Sample Selectionmentioning
confidence: 99%
“…From each record, the following information was collected by trained hospital residents: patient's age, sex, date of presentation, chief complaint, differential diagnosis, final diagnosis, medications, and the name of the treating physician. This process is explained in detail in Nakhle et al's study entitled Beirut Air Pollution and Health Effects-BAPHE study protocol and objectives [26]. The data was then entered into Microsoft Excel, inspected by the principal investigator, and validated by two senior physicians/epidemiologists who were part of the research team.…”
Section: Data Collectionmentioning
confidence: 99%